Kajian Kesiapsiagaan Bencana Banjir Berbasis Pentahelix di Kota Banjar Jawa Barat - Safira, Roro Afifah; Adiputra, Agung (Universitas Negeri Surabaya, 2023)
Flooding is a very common natural disaster in Indonesia. It is necessary to have a disaster risk management programme. This study aims to determine the disaster preparedness of the community for flood in the city of Banjar, West Java. Data were collected from the city government, regional disaster management agency, non-governmental organisations, BPS, earth shape maps from InaGeoportal, vulnerability map data, vulnerability maps and risk maps from the National Disaster Management Agency, and literature in the form of journals and books. The data collection techniques used by the researchers included questionnaires and documentation. The method of data analysis used was descriptive percentage and scoring analysis to analyse the frequency distribution of the level of preparedness of the community in the face of flood disasters.The data was obtained by providing questionnaires to the community which were filled in by the respondents and then calculating the total frequency of correct answers from each respondent. It can be seen that Banjar city has a high level of flood hazard, vulnerability and capacity, which means that it is important to take preparedness measures to reduce the adverse effects and anticipate the increase of recurrent floods.